2007
DOI: 10.1124/mol.106.032011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cocaine Administration Causes an Epigenetic Modification of Protein Kinase Cϵ Gene Expression in Fetal Rat Heart

Abstract: Protein kinase Cepsilon (PKCepsilon) plays a pivotal role in cardioprotection during cardiac ischemia and reperfusion injury. Recent studies demonstrated that prenatal cocaine exposure caused a decrease in PKCepsilon expression and increased heart susceptibility to ischemic injury in adult offspring, suggesting an in utero programming of PKCepsilon gene expression pattern in the heart. The present investigation aimed to elucidate whether an epigenetic mechanism, DNA methylation, accounts for cocaine-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…Our previous studies demonstrated that prenatal insults caused an epigenetic modification of the PKC gene in the fetal heart resulting in a down-regulation of PKC expression in the heart of adult offspring (Li et al, 2004;Bae et al, 2005;Zhang et al, 2007). A similar finding has been obtained in the present study showing that prenatal nicotine exposure significantly decreased cardiac PKC protein expression in adult offspring.…”
Section: Prenatal Nicotine and Cardiac Programming 335supporting
confidence: 79%
“…Our previous studies demonstrated that prenatal insults caused an epigenetic modification of the PKC gene in the fetal heart resulting in a down-regulation of PKC expression in the heart of adult offspring (Li et al, 2004;Bae et al, 2005;Zhang et al, 2007). A similar finding has been obtained in the present study showing that prenatal nicotine exposure significantly decreased cardiac PKC protein expression in adult offspring.…”
Section: Prenatal Nicotine and Cardiac Programming 335supporting
confidence: 79%
“…For instance, increased DNA methylation was observed in the OPRM1 gene in lymphocytes of former heroin users currently on methadone maintenance (Nielsen et al, 2009). Maternal exposure to cocaine was found to cause methylation of the AP-1 and SP1 binding sites and hyper-methylation of the promoter region of PKCε in the fetal rat heart Zhang et al, 2007Zhang et al, , 2009, as well as changes in the global methylation status of hippocampal pyramidal neurons (Novikova et al, 2008). Direct exposure to cocaine was found to cause hyper-methylation of the CDKL5 gene in the striatum (Carouge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…40 In addition, prenatal exposure to cocaine or to hypoxia causes methylation of the activator protein-1 binding site of the protein kinase C-⑀ gene (PKC-⑀); this, in turn, leads to decreased expression of the kinase, which has a cardioprotective function after cardiac ischemia-reperfusion injury. 89,90 However, this evidence was obtained in rats; the same issues must be studied in humans before the epigenetic modifications of PKC-⑀ can be used to identify people eligible for primary prevention measures.…”
Section: Early Detection Of Cvd For Primary Prevention: a Role For Epmentioning
confidence: 99%